Identifikasi Jamur Penyebab Onikomikosis Pada Kuku Jari Kaki Petani Sawah Di Desa Rajeg Kabupaten Tangerang - Mulyati; Rohadatul Aisy, Dzia Ulhaq; Wulandari, Destiana (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Fungi are eukaryotic microorganisms that can grow in damp places. Onychomycosis is a fungal infection of the nails, which causes nail damage affecting approximately 10% of the world's population. Rice farming is a job that has a high risk of onychomycosis due to high activity in a humid environment. The aim of this research was to determine the description of the fungus that causes onychomycosis in the toenails of rice farmers in Rajeg Village, Tangerang Regency.This research uses a descriptive observation method with data analysis presented in the form of univariate and bivariate tables. The research was carried out in May-June 2023, with 34 samples taken using the technique random sampling. The research results showed that the most positive results for onychomycosis infection occurred in rice farmers with female gender at 55.9% and the productive age group 26-65 years at 64.7%. Apart from that, onychomycosis infections often occur in farmers who have worked >5 years, amounting to 82.3%, with the habit of not using footwear when working at 91.2% and farmers who do not wash their toenails with soap at 64.7%. Based on research, it is known that the frequency distribution of the fungus that causes onychomycosis in rice farmers by direct examination was found to be 41.2% and by culture examination was found to be 91.2% with the largest species found, namelyAspergillus sp 46.7%. Based on the research results, it can be concluded that length of work, habit of using footwear, and habit of washing toenails with soap are several factors that influence the occurrence of onychomycosis infection in farmers.   Keywords           : Fungi, Onychomycosis, Rice Field Farmers